TANMANA BHOJANGATAH CHITAH (PSCHYE AND FOOD) (AYUSHDHARA, 2020)
Three million ago of the south Asian region, India had his own traditional system of medicine which known as Ayurveda. It explains the Rasa, Guna, Virya, and Vipaka of the Dravyas (Medicinal as well as food materials). It gives us some unique concepts to take the food (Asta ahar vidhi Visheshayatana) and its effect on body and mind. Ayurveda is science of wellness which primarily deals in food and behavioural aspects. Food and psychology has a good relation in Ayurveda. Emotions and psychological state has a very profound role in the proper digestion and metabolism of food. Ayurveda explains different psychological and emotional state of digestion, and establishment of ground rule that we should have food with psychological relaxation without any mental disturbance. As well as impact of occupational stress and weight conscious diet on digestion according to modern medical science is discussed. Ayurveda already have many references in many places of different Samhitas especially in Charak, Sushrut and Astang. They clearly told that we have to follow the rules of Asht-Aharvidhi Visheshayatana and they coded that, food has his own properties which helps to enhance the physical factors as well as mental factors of the body. Balanced food habits complete the both Prayojana of the Ayurveda which is “Swasthasya Swastha Rakshanam and Aturasya Vikara Prashamanm Cha”. Emotional status of the person at the food taking time also plays an important role of its digestion and metabolism in the body. A big question arise here that whether first psychology effect in digestion of food or food affecting the psychology of the person.